Edutainment sebagai Strategi Komunikasi Pembangunan dalam Media Digital: Analisis Teori Sabido pada Konten YouTube Watchdoc Documentary “Tanah Moyangku” - Nina Kusumawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Digital media is currently a primary means of development communication. Edutainment, a combination of education and entertainment, is an effective strategy for conveying social messages in an engaging manner. This study analyzes the content of the YouTube Watchdoc documentary